Implementasi Kode Etik Profesi Hakim dalam Menekan Penyalahgunaan Wewenang di Pengadilan - Akbar, Muhamad Aria Torik; Kayowuan L, Kayus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the implementation of the Code of Ethics and Guidelines for Judges' Conduct (KEPPH) as the main instrument in suppressing abuse of authority in the Indonesian judiciary. Using normative legal research methods, this study analyzes legal norms, doctrines, and court decisions related to supervision and enforcement of discipline against judges. The results of the study indicate that the mechanism of supervision and enforcement of discipline has been running structurally through the role of the Supreme Court (MA) and the Judicial Commission (KY), although it still faces challenges such as limited resources, less than optimal coordination, and an unstable legal culture. The most frequent violations of the code of ethics include abuse of authority, bribery, and gratification, which have a serious impact on public trust in the judicial institution. Effective enforcement of the KEPPH is considered very important to strengthen the integrity of judges, improve the quality of decisions, and build a clean, transparent, and accountable judicial system in Indonesia.